Intentional violent deaths of Blacks in late slavery - Eufrazio, Francisco Flavio (Argumentum, 2024)
This article denounces the permanent presence of the decline of the Black population due to intentional violent deaths. It reaffirms the Eusébio de Queiroz Law as a concrete contributor to the mortality of enslaved Black children and analyses the massacre of Blacks during the Paraguayan War. It argues, based on a review of literature, that late slavery produced harmful consequences for the enslaved population. One consequence concerns the population fall that continues to the present day through the intentional violent deaths of Blacks.